Pseudo-Reality from the Context of Reader-Author Relationship Through Wattpad Comments Section: A Simulation Theory from Jean Baudrillard - Anggraini, Purwati; Suyatno; Tjahjono, Tengsoe; Widodo, Joko (Universitas Muhammadiyah Malang, 2023)
The development and issues within the Wattpad platform require research on the pseudo-reality in virtual communication between its readers and author. The pseudo-reality can help determine the communication type in the comments section: positive or negative. Therefore, this research can determine to what extent readers can accept the pseudo-reality that might occur during the interaction between them and the author. This research describes the pseudo-reality in the communication between the readers and author on the Wattpad platform by using the descriptive qualitative method based on a theory by Jean Baudrillard. The data source is the communication record between readers and author in BYBcool’s comments section of cyber fiction entitled Lost World, Zystrome: The Exordium Outsider, El Libro, dan Outsider by Rania Thahirah. Data collection is in the form of chat records between readers and authors that contain pseudo-reality. The steps taken in data collection include data selection, reading the data collection, documenting data collection, designing the research instrument, inserting data into the data capture table, and coding it. The data analysis step in this research comprises describing and interpreting data inductively, simultaneous data collection, and analyzing data using a particular content analysis technique before finally drawing a conclusion. The research result revealed the existence of pseudo-reality in the Wattpad comment section. The author’s responses were a manipulation attempt to create a good image, show concern over the readers and broad insight and incredible ideas, and get plenty of fans. Simultaneously, the author created pseudo-reality by choosing neutral words to avoid potential conflicts, responding to readers’ comments accordingly, and using appropriate emoticons and emojis with the most suitable expression. Good communication is essential for authors to build a close relationship with their readers.